2000
DOI: 10.1046/j.1365-2540.2000.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation among northern and southern populations of the moor frog Rana arvalis Nilsson in central Europe

Abstract: Starch gel electrophoresis and morphometric characters were used to assess the geographical variation between 14 populations of the moor frog, Rana arvalis, from northern and southern areas in Central Europe. Six of the 13 screened allozyme loci were polymorphic (95% criterion). No fixed differences in allele composition between the two regions were found. Some of the alleles were region specific. Genetic variability as measured by expected heterozygosity ( He) and number of alleles per locus was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 21 publications
(5 reference statements)
4
22
1
3
Order By: Relevance
“…The observed heterozygosity (H o ) ranged from 0.08 to 0.14 (average 0.11) was higher than that (0.10) reported by Raginski and Babik (2000) in R. arvalis. The expected heterozygosity (H e ) was found to be 0.16 in the present study, which was similar to those obtained by Rafiniski and Babik (2000) and Khan et al (2002).…”
Section: Discussioncontrasting
confidence: 55%
“…The observed heterozygosity (H o ) ranged from 0.08 to 0.14 (average 0.11) was higher than that (0.10) reported by Raginski and Babik (2000) in R. arvalis. The expected heterozygosity (H e ) was found to be 0.16 in the present study, which was similar to those obtained by Rafiniski and Babik (2000) and Khan et al (2002).…”
Section: Discussioncontrasting
confidence: 55%
“…Such influence of time since colonisation was often found in empirical studies of IBD (e.g. Rafinski and Babik 2000;Castric and Bernatchez 2003).…”
Section: Discussionmentioning
confidence: 66%
“…For several terrestrial and aquatic organisms, suture zones in Central (for example Taberlet et al, 1995) (Figure 3a; Babik et al, 2004), and even though the haplotype lineages in many parts overlap each other, a slight east-west separation can be identified. Thus, given a phylogenetic structuring like this, it has been suggested that the moor frog survived the last glacial period in multiple refugial areas (Rafiń ski and Babik, 2000;Babik et al, 2004 from clade AI can also be found in the west, but they are more widespread in the eastern parts. Therefore, a refugium situated in south-eastern Russia-or even further east in Siberia or Kazakhstan-has been suggested (Rafiń ski and Babik, 2000;Babik et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, given a phylogenetic structuring like this, it has been suggested that the moor frog survived the last glacial period in multiple refugial areas (Rafiń ski and Babik, 2000;Babik et al, 2004 from clade AI can also be found in the west, but they are more widespread in the eastern parts. Therefore, a refugium situated in south-eastern Russia-or even further east in Siberia or Kazakhstan-has been suggested (Rafiń ski and Babik, 2000;Babik et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation